Responsiveness of Noninvasive Continuous Cardiac Output Monitoring During the Valsalva Maneuver. (February 2020) - Delaney, L. J.; Bellomo, R.; van Haren, F.
To describe the baseline hemodynamic variables and response time of hemodynamic changes associated with the Valsalva maneuver using noninvasive continuous cardiac output monitoring (Nexfin). Hemodynamic monitoring provides an integral component of advanced clinical care and the ability to monitor response to treatment interventions. The emergence of noninvasive hemodynamic monitoring provides clinicians with an opportunity to monitor and assess patients rapidly with ease of implementation. However, the responsiveness of this method in tracking dynamic changes that occur has not been fully elucidated. A prospective observational study was conducted involving 44 healthy volunteers (age = 38 ±12 years). Participants performed a Valsalva maneuvers to illicit dynamic changes in blood pressure, cardiac output, cardiac index, systemic vascular resistance index (SVRI), and stroke volume. Changes in these hemodynamic parameters were monitored while performing repeated standardized Valsalva maneuvers. Baseline hemodynamic values were obtained in all 44 participants, and showed an interaction with age, accompanying a significant decline in cardiac index ( r = –.66, p < .05) and stroke volume ( r = –.68, p < .05), and an increase in SVRI ( r = .67, p < .05) with increasing age. The Valsalva maneuver, performed in 20 participants, resulted in a change of 10% from baseline blood pressure and cardiac index, which was detected within 4.53 s ( SD = 4.36) and 3.31 s ( SD = 2.21), respectively. Noninvasive continuous cardiac monitoring demonstrated the ability to rapidly detect logical and predictable hemodynamic changes. These observations suggest that such Nexfin technology may have useful clinical applications.